Antihyperlipidemic and antiatherogenic activities of Terminalia pallida Linn. fruits in high fat diet-induced hyperlipidemic rats - M T Sampathkumar; R B Kasetti; S A Nabi; P Renuka Sudarshan; S Swapna; C Apparao (Journal of Pharmacy and Bioallied Sciences, 2011)
Hyperlipidemia contributes significantly in the manifestation and development of atherosclerosis and coronary heart disease (CHD). Although synthetic lipid-lowering drugs are useful in treating hyperlipidemia, there are number of adverse effects. So the current interest has stimulated the search for new lipid-lowering agents with minimal side effects from natural sources. The present study was designed to investigate the antihyperlipidemic and antiatherogenic potentiality of ethanolic extract of Terminalia pallida fruits in high fat diet-induced hyperlipidemic rats. T. pallida fruits ethanolic extract (TPEt) was prepared using Soxhlet apparatus. Sprague-Dawley male rats were made hyperlipidemic by giving high fat diet, supplied by NIN (National Institute of Nutrition), Hyderabad, India. TPEt was administered in a dose of 100 mg/kg.b.w./day for 30 days in high fat diet-induced hyperlipidemic rats. The body weights, plasma lipid, and lipoprotein levels were measured before and after the treatment. TPEt showed significant antihyperlipidemic and antiatherogenic activities as evidenced by significant decrease in plasma total cholesterol, triglycerides, low-density lipoprotein cholesterol, and very low-density lipoprotein cholesterol levels coupled together with elevation of high-density lipoprotein cholesterol levels and diminution of atherogenic index in high fat diet-induced hyperlipidemic rats. There was a significantly reduced body weight gain in TPEt-treated hyperlipidemic rats than in the control group. The present study demonstrates that TPEt possesses significant antihyperlipidemic and antiatherogenic properties, thus suggesting its beneficial effect in the treatment of cardiovascular diseases.